Peningkatan Kesadaran Siswa Tentang Bahaya Media Sosial Melalui Maksimalisasi Esensi Self Pada Pendekatan Konseling Self (CaRL Rogers - Ismayani Ismayani; Feby Angel Auralia; Gusman Lesmana (Journal on Education, 2025)
The aim of this research is to determine the effectiveness of the self-counseling approach technique in increasing female students' awareness of the dangers of social media. The research method used also uses qualitative methods by looking for theoretical references that are relevant to the observed phenomena. Observations were carried out at SMA MUHAMMADIYAH 01 MEDAN. The results of research on self-counseling approach techniques can be used to increase awareness about the dangers of social media among high school students. This is proven by changes in the behavior patterns of the subjects studied who experienced changes in the discipline of using social media after the subjects underwent the counseling process.